Life cycle assessment of rice straw-based power generation in Malaysia - Mohd Shafie, Shafini; Masjuki, H.H.; Mahlia, T.M.I. (Elsevier Ltd, 2014)
This paper presents an application of LCA (Life Cycle Assessment) with a view to analyzing the environment aspects of rice straw-based power generation in Malaysia.It also compares rice straw-based power generation with that of coal and natural gas. GHG (Greenhouse gas) emission savings were calculated. It finds that rice straw power generation can save GHG (greenhouse gas) emissions of about 1.79 kg CO2-eq/kWh compared to coal-based and 1.05 kg CO2-eq/kWh with natural gas based power generation. While the development of rice straw-based power generation in Malaysia is still in its early stage, these paddy residues offer a large potential to generate electricity because of their availability.Rice straw power plants not only could solve the problem of removing rice straw from fields without open burning, but also could reduce GHG emissions that contribute to climate change, acidification, and eutrophication, among other environmental problems.